Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the solution set of the compound inequality [tex]\(3x + 2 \leq 5x + 6 \leq 6x + 7\)[/tex], we need to break it down into two individual inequalities and solve each one separately. Let's break it into two separate inequalities:
1. [tex]\(3x + 2 \leq 5x + 6\)[/tex]
2. [tex]\(5x + 6 \leq 6x + 7\)[/tex]
### Solve the first inequality [tex]\(3x + 2 \leq 5x + 6\)[/tex]:
1. Start by subtracting [tex]\(3x\)[/tex] from both sides:
[tex]\[ 2 \leq 2x + 6 \][/tex]
2. Next, subtract 6 from both sides:
[tex]\[ 2 - 6 \leq 2x \][/tex]
[tex]\[ -4 \leq 2x \][/tex]
3. Finally, divide both sides by 2:
[tex]\[ -2 \leq x \][/tex]
This simplifies to:
[tex]\[ x \geq -2 \][/tex]
### Solve the second inequality [tex]\(5x + 6 \leq 6x + 7\)[/tex]:
1. Start by subtracting [tex]\(5x\)[/tex] from both sides:
[tex]\[ 6 \leq x + 7 \][/tex]
2. Next, subtract 7 from both sides:
[tex]\[ 6 - 7 \leq x \][/tex]
[tex]\[ -1 \leq x \][/tex]
This simplifies to:
[tex]\[ x \geq -1 \][/tex]
### Combine the solutions of the two inequalities:
- From the first inequality, we have [tex]\(x \geq -2\)[/tex].
- From the second inequality, we have [tex]\(x \geq -1\)[/tex].
Since [tex]\(x \geq -1\)[/tex] is a stricter constraint than [tex]\(x \geq -2\)[/tex], the solution to the compound inequality is [tex]\(x \geq -1\)[/tex].
Therefore, the solution set of [tex]\(3x + 2 \leq 5x + 6 \leq 6x + 7\)[/tex] is [tex]\(x \geq -1\)[/tex].
1. [tex]\(3x + 2 \leq 5x + 6\)[/tex]
2. [tex]\(5x + 6 \leq 6x + 7\)[/tex]
### Solve the first inequality [tex]\(3x + 2 \leq 5x + 6\)[/tex]:
1. Start by subtracting [tex]\(3x\)[/tex] from both sides:
[tex]\[ 2 \leq 2x + 6 \][/tex]
2. Next, subtract 6 from both sides:
[tex]\[ 2 - 6 \leq 2x \][/tex]
[tex]\[ -4 \leq 2x \][/tex]
3. Finally, divide both sides by 2:
[tex]\[ -2 \leq x \][/tex]
This simplifies to:
[tex]\[ x \geq -2 \][/tex]
### Solve the second inequality [tex]\(5x + 6 \leq 6x + 7\)[/tex]:
1. Start by subtracting [tex]\(5x\)[/tex] from both sides:
[tex]\[ 6 \leq x + 7 \][/tex]
2. Next, subtract 7 from both sides:
[tex]\[ 6 - 7 \leq x \][/tex]
[tex]\[ -1 \leq x \][/tex]
This simplifies to:
[tex]\[ x \geq -1 \][/tex]
### Combine the solutions of the two inequalities:
- From the first inequality, we have [tex]\(x \geq -2\)[/tex].
- From the second inequality, we have [tex]\(x \geq -1\)[/tex].
Since [tex]\(x \geq -1\)[/tex] is a stricter constraint than [tex]\(x \geq -2\)[/tex], the solution to the compound inequality is [tex]\(x \geq -1\)[/tex].
Therefore, the solution set of [tex]\(3x + 2 \leq 5x + 6 \leq 6x + 7\)[/tex] is [tex]\(x \geq -1\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.